XPS characterization of tribo-layer formation on the steel lubricated with crude and epoxidized jatropha oil under boundary lubrication - Lubis, A.M.H.S. (Emerald Group Publishing Ltd., 2017)
The composition of the tribo-layer formed during sliding of steel in the presence of crude jatropha oil (CJO) and epoxidized jatropha oil (EJO) under boundary lubricant application was investigated using energy-dispersive X-ray and X-ray photo spectroscopy analyses. Utilizing four ball method according to ASTM 4192, EJO showed better wear preventive properties and a lower friction coefficient compared to CJO. CJO and EJO oxidation led to oil chemisorption to steel surface causing formation of protective layers for the steel surface. The layers were constructed from inorganic oxide in the form of iron oxides and silicon oxide together with organic layers in form of aldehyde, ketone, and carboxylic acid. The formation and removal of this layer from rubbing sites are considered to impact wear-preventive and friction behavior of steel lubricated with CJO and EJO.